2013
DOI: 10.1589/jpts.25.1087
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Prayer Movements as an Alternative Therapy in the Treatment of Erectile Dysfunction: A Preliminary Study

Abstract: [Purpose] Our objective was to assess the effect of salat and mimicking salat movements and postures on subjects with erectile dysfunction. [Methods] Ten volunteers were recruited in this study. Subjects who were Muslims (Group I) were asked to perform their daily salat and a new intervention of an additional 12 movement cycles of salat for three sessions a week. Non-Muslim subjects (Group II) were taught to mimic salat movements, and were asked to perform a total of 12 movement cycles without reading the reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Islamic ritual prayer, or salat, consists of a set of physical postures, or intentional movements including standing, bowing, prostrating and sitting, performed a minimum of five times per day (Doufesh, Ibrahim, & Safari, 2016). Considered to be a mild to moderate form of physical activity, salat provides psychological, musculoskeletal and neurophysiological effects (Ibrahim, Sian, Shanggar, & Razack, 2013). This ritual prayer can be compared to tai chi and yoga as it involves the movement of the whole body as well as providing those practicing a meditative platform (Doufesh et al, 2016).…”
Section: Ritual Prayermentioning
confidence: 99%
“…Islamic ritual prayer, or salat, consists of a set of physical postures, or intentional movements including standing, bowing, prostrating and sitting, performed a minimum of five times per day (Doufesh, Ibrahim, & Safari, 2016). Considered to be a mild to moderate form of physical activity, salat provides psychological, musculoskeletal and neurophysiological effects (Ibrahim, Sian, Shanggar, & Razack, 2013). This ritual prayer can be compared to tai chi and yoga as it involves the movement of the whole body as well as providing those practicing a meditative platform (Doufesh et al, 2016).…”
Section: Ritual Prayermentioning
confidence: 99%
“…One study showed that Salat exercises improved symptoms in women with UI, 7 whilst another demonstrated that it increases blood flow to the pelvic floor muscles. 8 This physical movement can treat and rehabilitate the cardiovascular, genitourinary system, at the same time improve impotence in men, quality of sex and genital muscle recovery 9 which ultimately imply its positive effect to the pelvic floor muscle. Given the diverse benefit of Salat steps, we proposed a study term "Hyacinth" exercise, which combined PFE and Salat steps to see its synergistic effect and hoping to evaluate its effectiveness when compared to PFE alone.…”
Section: Introductionmentioning
confidence: 99%
“…10 Contributions There is no similar study performed before on effectiveness of this exercise on urinary incontinence, we based the hypothesis on its positive effect in the treatment of erectile dysfunction. 11 In a pilot study 7 done in our center, improvement in bladder function which was objectively measured with the Female Pelvic Floor Questionnaire (FPFQ) was seen earlier in the Salat plus PFE arm as compared to PFE alone. Based on this, we sought to perform a powered study with a larger cohort and longer follow up period.…”
Section: Introductionmentioning
confidence: 99%
“…The regular practice of Salah may positively impact an individual’s health, including the health of the musculoskeletal, cardiovascular, and nervous systems [ 14 , 20 22 ].…”
Section: Introductionmentioning
confidence: 99%